Silício na nutrição mineral e acúmulo de alumínio em plantas de arroz de terras altas - Freitas, Lucas Barbosa De [UNESP] (2015)
Silicon is able to protect plants against various biotic and abiotic stresses, including aluminum stress. However, the interaction between silicon and aluminum is still little known, since there are several hypotheses to justify the silicon role on aluminum stress alleviation. This study aimed at evaluating the effect of silicon application on contents and accumulation of macro and micronutrients, aluminum and silicon on shoots of upland rice grown under aluminum stress, as well as the chemical characteristics of the soil after harvest. The experimental design was randomized blocks, in a 2 x 5 factorial arrangement, with four replications. Treatments consisted of two upland rice cultivars (BRS Talento -aluminum non-tolerant; Guarani -aluminum tolerant) and five silicon doses (0 mg dm-3, 30 mg dm-3, 60 mg dm-3, 90 mg dm-3 and 120 mg dm-3). The silicon applied increases the silicon content in the plant and soil and decreases the aluminumcontent in shoots, however, it does not increase the macro and micronutrients absorption and does not change the soil aluminum content and pH.